Rat thimet oligopeptidase: large-scale expression in Escherichia coli and characterization of the recombinant enzyme. - McKie, N (1995)
The coding sequence for rat testis thimet oligopeptidase (TOP) (EC 3.4.24.15) was placed under the control of the T7 polymerase/promoter system. Cultures of Escherichia coli transfected with the resulting plasmid expressed the enzyme as a soluble cytoplasmic protein. Medium-scale cultures allowed isolation of the enzyme in quantities of tens of milligrams. The availability of the recombinant enzyme permitted the determination of such chemical properties as epsilon 280 (48,960), zinc content (2 atom/molecule) and available thiol content (8-10/molecule) for TOP. The recombinant enzyme showed the catalytic activities previously reported for the naturally occurring enzyme, so that we can now conclude with confidence that these are all due to TOP and there is no need to postulate the existence of separate 'Pz-peptidase' or 'endo-oligopeptidase A' enzymes.